Framing risk in China: precarity and instability in the stories of Li Yiyun*. Issue 3 (16th April 2017) - Matthews, Graham J.
ABSTRACT: Drawing on the 'risk society' approach of Ulrich Beck and Anthony Giddens, which is characterised by the constant state of concern, anxiety, and dread people feel in relation to environmental threats to human health, this article explores the ways in which the Chinese author Li Yiyun presents the relationship between Chinese and Western conceptions of risk. By orchestrating a series of imagined encounters between Chinese nationals and Chinese living overseas, Li's fiction challenges ethnocentric conceptions of identity and signals the inadequacy of any understanding of risk that is not culturally, historically and geographically situated. Li's narratives indicate the ways in which new conceptions of risk, influenced by but not identical to the uncertain dynamics of the 'risk society', are developing in post-Mao China. Whereas the 'risk society' is the result of scepticism towards modernity, contemporary Chinese culture is broadly optimistic regarding progress and industrialisation. Li's work is unique insofar as it signals the ways in which conceptions of risk from the West are subtly interacting with and altering conceptions of fragility and uncertainty in China and in turn sheds light on the constructed nature of 'risk' under globalisation.